THE COMMUNICATIVE SPACE OF UKRAINIAN CULTURE OF THE LATE XIX- EARLY XX CENTURIES AS A FACTOR IN THE DEVELOPMENT OF NATIONAL IDENTITY - Matyukhina, Olexandra (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2022)
Introduction.Today the implementation of sustainable development goals by the world community and Ukraine, in particular, the process of the communicative space of Ukrainian culture forming at the turn of the XIX-XX centuries is acquiring new relevance. The aim is to study the features of the formation of the communicative space of Ukrainian culture in the late XIX and early XX centuries. The tasks are to outline the factors of a common semiosphere formation utilizing artistic culture and the dissemination of joint meanings, symbolic codes by educational organizations. Research methodology. The nature of the research determines its methodological basis; the paper uses a comparative, socio-cultural, and a cultural-historical approaches in their dialectical unity. To solve individual research problems, the method of systems analysis, the principles of ascent from the abstract to the concrete, and consistency were applied. Research results. Noting the diversity of styles and trends in the artistic culture of the XIXandearly XXcenturies, special attention is paid to symbolism. It is noted that symbolism determined the continuity in the formation of the communicative space of Ukrainian culture, its close connection with the culture of the people. And this provided an intensive affirmation and spread of the communicative space of the modern political nation with its striving for sovereignty as a goal. Discussion. Representatives of the Ukrainian culture objectively revived and created a communicative space corresponding to the challenges of the era. If fiction formed a communicative space with values, meanings, images, new ways of interpretation, then fine art created their visual embodiment, formed a visual series. The role of educational activities of cultural societies as repeaters of the achievements of national culture among the masses is noted. Conclusion. Society as a whole is formed in the process of communication. A component of this process is the creation and reproduction of culture. Ukrainian culture became a cultural project of the late XIX and early XX centuries.Writers, poets, painters, sculptors, architects, theater workers created a communicative space corresponding to the deep needs of the nation by the process of their creativity and its results. The correlation of the space of national culture with the space of art contributed to its development and establishment as the basis of the nation’s communicative space. The Ukrainian society is again faced with the task of developing a common communicative space for the implementation of the interaction between members of society and the achievements of the past can enrich the present.